2012
DOI: 10.1002/psc.2425
|View full text |Cite
|
Sign up to set email alerts
|

Peptaibols from two unidentified fungi of the order Hypocreales with cytotoxic, antibiotic, and anthelmintic activities

Abstract: As part of an ongoing investigation of filamentous fungi for anticancer leads, an active culture was identified from the Mycosynthetix library (MSX 70741, of the order Hypocreales, Ascomycota). The fungal extract exhibited cytotoxic activity against the H460 (human non-small cell lung carcinoma) cell line, and bioactivity-directed fractionation yielded peptaibols 1–12 and harzianums A (13) and B (14). Structure elucidation of 1–12 was facilitated by high-resolution MS/MS obtained on a Thermo LTQ Orbitrap XL us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 50 publications
4
99
0
Order By: Relevance
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
“…The peptaibols have been intensively studied because of their abilities to form pores in the outer membranes of cells; these pore-forming capabilities result in most compounds in this class exhibiting nonspecific cytotoxic properties toward bacterial, fungal, and mammalian cells (15,17). The effects of peptaibols on mammalian cells tend to be relatively modest, causing the loss of cell viability at concentrations in the mid-to-high micromolar range (18)(19)(20)(21)(22)(23)(24)(25). With many hundreds of peptaibols reported, finding new peptaibol analogs that possess an alternative mode of biological activity would be an impracticable prospect if one relied solely on either chemically driven or genome-based approaches to identify candidate molecules.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies and as part of our continued effort to quantify the chemical diversity of fungal isolates [6], herein we expand the analysis to a larger set of 207 compounds described by our group [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] that represent twice the size of the dataset analyzed in 2012. In the current analysis, we employed molecular fingerprints as distinct molecular representations not analyzed in the previous study; also we emphasized the evaluation of molecular complexity that may have a significant impact in drug discovery endeavors, since this feature has been associated with target selectivity (and potential toxicity).…”
Section: Special Focus Issue -Antifungal Drug Discoverymentioning
confidence: 99%